Association of Recurrent Aphthous Ulcer Among Tobacco Users - A Retrospective Study - AISHWARYA. S,; DHARMAN, SREEDEVI; SURESH.V, (The journal of contemporary issues in business and government, 2020)
Recurrent Aphthous Ulcer(RAU) is one of the most common painful,recurrent oral mucosal disease that can be single or multiple seen among patients. These present as round, or ovoid ulcers, with circumscribed margins, having yellow or gray floors and are surrounded by erythematous haloes. The etiology of Recurrent Aphthous Ulcer always remains unclear. Symptomatic treatment is usually done which usually includes topical corticosteroids. The aim of the study is to find out the association of recurrent aphthous ulcer among the people who use smoking and smokeless form of tobacco.The study was carried out for a 1 year period ( June 2019 to April 2020) .229 patients data (213 males and 6 females) who visited Saveetha dental college and hospitals, Chennai were included. Statistical analysis was done by chi square test. In the study, it is observed that only 3.5% of the males who had tobacco usage habits were diagnosed with Recurrent Aphthous Ulcer. The patients aged between 31-40 years had higher prevalence of Recurrent Aphthous Ulcer (61.15%) compared to other age groups. Among the tobacco users only 1.75% of RAU was prevalent among smoking and smokeless groups respectively. There is no significant association between tobacco users and recurrent aphthous ulcer p value 0.625,p (>0.05). Minor aphthous ulcer (87.5%) were more commonly present compared to major apthous ulcer among tobacco users. Within the limitations of the study, among the tobacco usage patients, males are more prevalent for Recurrent Aphthous Ulcer than females and occurrence of RAU among tobacco users were less.Though there is no association,anti tobacco counselling to be conducted frequently to educate them from harmful effects of tobacco.